A new method to predict the content changes of aroma compounds during the aging process of Niulanshan Baijiu using the GM (1, 1) gray model. (21st November 2021) - Wang, Zhen; Wei, Jinwang; Wang, Ying; Zhu, Tingting; Huang, Mingquan; Wu, Jihong; Xu, Youqiang; Zhang, Jinglin; Wang, Bowen
Abstract: Niulanshan Baijiu (NLS), a kind of light‐flavor Baijiu, is very popular in China. The gray model [GM (1, 1)], a mathematical model, is used to predict the content changes of key odorants in NLS during the aging process. First, the smell experiment of NLS was carried out by gas chromatography‐olfactometry‐mass spectrometry (GC‐O‐MS). Then, 34 aroma compounds in NLS aged four different years were identified and quantitated, calculated the OAVs of these aroma compounds, there were 18 compounds with OAVs >1, which were considered as important aroma compounds in NLS, and finally, the gray prediction was carried out by modeling the content of these compounds. The correlations between the predicted values and actual values were as high as 0.9969. This is the first time that GM (1, 1) is used in liquor content analysis, and the good prediction results show the applicability of GM (1, 1) in predicting the content change of compounds during Baijiu aging. Abstract : This study identified a new research method for Baijiu aging and for the first time conducted mathematical modeling based on chromatographic analysis.